30 Rock. Season 3 [videorecording (DVD)] - Fey, Tina, 1970-; Morgan, Tracy, 1968-; Krakowski, Jane; McBrayer, Jack, 1973-; Adsit, Scott, 1965-; Friedlander, Judah; Baldwin, Alec, 1958- (Universal Studios Home Entertainment, 2009)
Go behind-the-scenes of a live sketch comedy show. Watch as Jack comes back to GE; Liz gets a visit from an adoption agency caseworker; Liz sits next to Oprah on her flight from Chicago to New York; Tracy and Jenna conduct a 'social experiment;' Jack hooks up with Liz's psycho ex-roommate; Liz thinks she has found the perfect mate; Don Geiss wakes from his coma; Jack falls in love with his mother's nurse; Liz has a disastrous first date; Jack gets the writers to come up with a name for GE's new pocket microwave; Liz launches a plan to find Jack's biological father.